Sorcery, rights, and cosmopolitics among the Tau-Buhid Mangyan in Mts. Iglit-Baco National Park - Rosales, Christian A. (Aghamtao, 2019)
The refusal of the Tau-Buhid to be intruded upon by the Philippine Government in their ancestral domain is intensfying. The State is unaware that resistance among the inhabitants in the remote regions of Mindoro is grounded in their practice of an offensive magic called "amurit". Although this term appears recurrently in mediatory discussions, it is dismissed by government agents who view it as an excuse to avoid compliance with State law, and for lack of 'scientific validation'.